Social support, discrimination, and Self-Esteem in LGBTQ + high school and Post-Secondary students. Issue 3 (3rd July 2022) - Taylor, Kirstie; Coulombe, Simon; Coleman, Todd A.; Cameron, Ruth; Davis, Charlie; Wilson, Ciann L.; Woodford, Michael R.; Travers, Robb
Abstract: LGBTQ+ (lesbian, gay, bisexual, transgender, queer, plus) people, compared to their heterosexual and/or cisgender (non-transgender) counterparts, are more likely to be discriminated against based on their gender or sexual identities. Drawing on data from The OutLook Study in Waterloo Region, Ontario, Canada this paper examines discrimination and social support among high school and post-secondary students, and how they are related to self-esteem. We found that transgender students in high school reported significantly higher levels of direct transphobia and of victimization compared to transgender post-secondary students. We found indirect homophobia and indirect transphobia had a significant adverse relationship to self-esteem. Further, social support from friends was related to higher self-esteem for cisgender LGBQ students, but not for transgender students. These findings have the potential to inform school-based policies and mental health interventions in support of improved wellbeing for LGBTQ + students.